Building a Supportive Learning Environment: A Qualitative Study on Conducive School Culture in Public Secondary Schools - Khan Sher; Prof. Dr. Hafiz Muhammad Inamullah (Social Science Review Archives, 2025)
A conducive school culture is essential to promote academic excellence, encouraging students overall development, and enhancing teacher effectiveness at the secondary school level. The aim of this study was to investigate the contribution of curricular and co-curricular activities, parental involvement and administrative practices in a conducive school culture for the overall wellbeing of the student. The nature of this study was purely qualitative where the sample size was kept small and smart; the data was collected through semi-structured interviews from the five elementary and secondary school principals in the district of Khyber, Khyber Pakhutnkhwa. The data was thematically analyzed and the study explored the importance of community and school relationship, parental connection with school administration, elimination of corporal punishment through parental support and Jarga system to discuss students’ affairs for a conducive school culture in elementary and secondary schools in the merged district of Khyber. Furthermore, this study recommended for a favorable educational climate where every student and teacher contributes meaningfully, targeted professional programs for teachers, school safety protocol and active participation of the parents and community with school administration